2007
DOI: 10.1002/cncr.22505
|View full text |Cite
|
Sign up to set email alerts
|

Patients with differentiated thyroid cancer have a venous gradient in thyroglobulin levels

Abstract: BACKGROUND.Although serum thyroglobulin (Tg) is an excellent marker for detecting recurrent or persistent differentiated thyroid cancer (DTC), it is unreliable in patients who have positive anti‐Tg antibodies. Furthermore, a growing number of patients with DTC have elevated Tg levels but no detectable disease on radioiodine scanning or other imaging studies. The objective of this study was to determine whether a gradient in Tg protein level exists in patients with DTC.METHODS.Fifteen patients who underwent thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Furthermore, conventional histology fails to provide prognostic and therapeutic information for TC. Some biomarkers, such as thyroglobulin (Tg) (7,8), galectin-3 (9) and HBME-1 (10), have been used in clinical practice for the diagnosis of PTC; however, the sensitivity and specificity of these biomarkers are low, and only a small fraction of these biomarkers can be used as diagnostic or prognostic biomarkers. Therefore, it is essential to develop novel diagnostic and prognostic biomarkers for PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, conventional histology fails to provide prognostic and therapeutic information for TC. Some biomarkers, such as thyroglobulin (Tg) (7,8), galectin-3 (9) and HBME-1 (10), have been used in clinical practice for the diagnosis of PTC; however, the sensitivity and specificity of these biomarkers are low, and only a small fraction of these biomarkers can be used as diagnostic or prognostic biomarkers. Therefore, it is essential to develop novel diagnostic and prognostic biomarkers for PTC.…”
Section: Introductionmentioning
confidence: 99%
“…Serum Tg level is the most commonly used biochemical marker to detect the persistent or recurrent disease in patients with DTC. It was reported that approximately 15% of thyroid cancer survivors have Tg-positive but radioiodine-negative tumors [9]. Thus, documentation of a venous gradient in Tg levels in patients with DTC is a new investigational topic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of venous sampling for Tg in patients with DTC is not clearly known. In a recent study, Kebebew and Reiff showed that 15 patients who underwent thyroidectomy and/or lymph node dissection for primary and persistent or recurrent DTC had a venous gradient in Tg levels, and also they suggested that venous sampling for Tg may be used to localize DTC in patients who have high or increasing Tg levels but negative imaging studies [9]. Similarly, according to the results of this study, there is a significant venous gradient between the Tg levels of venous samples adjacent to primary tumor and distant circulation in patients with DTC.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 24 patients in the study 22 patients had well differentiated carcinomas [3] of follicular cell origin. These patients were categorized into low and high risk groups based on the AMES categorization scheme [10].…”
Section: Risk Categorizationmentioning
confidence: 99%